Evaluasi Pembelajaran Berbasis Digital di Sekolah Dasar: (Studi Observasi pada Sekolah Internasional dan Nasional) (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The development of digital technology has driven significant transformations in learning and assessment practices at the elementary school level. Digital-based learning assessment is no longer viewed merely as a tool to measure learning outcomes, but as an integral component of a continuous, interactive, and contextual learning process. This study aims to evaluate the implementation of digital-based learning assessment in elementary schools through an observational study of international and national schools. A qualitative descriptive approach was employed. Data were collected through classroom observations, brief interviews with teachers and students, and documentation in six elementary schools located in Jakarta, Bandung, and Pesisir Selatan Regency. The findings indicate that international and private schools have systematically implemented digital-based assessment through the use of Learning Management Systems (LMS), digital quiz applications, and electronic portfolio assessments, supported by adequate infrastructure and high levels of teachers’ digital competence. In contrast, national public schools demonstrate adaptive efforts by utilizing simpler digital tools such as projectors, interactive quiz applications, and class-based or group-based assessment models, despite facing limitations in infrastructure and the precision of individual assessment. This study concludes that digital-based learning assessment in Indonesian elementary schools is currently in a positive transitional phase and requires strengthened infrastructure, continuous teacher professional development, and the development of contextual and sustainable assessment models.